Advancing Processing Technologies for Designed Geopolymers: 3D Printing and Mechanical Machining - Toniolo, Nicoletta; Bednarzig, Vera; Roether, Judith; Rost, Harald; Boccaccini, Aldo R. (Interceram, 2019)
Abstract: Geopolymers continue to attract interest owing to their good mechanical properties in combination with the ecofriendly fabrication process. However, the applications of geopolymers are still restricted to a limited field, mainly as construction materials. Designing and fabricating components of complex, intricate shape for applications beyond building materials may represent a useful approach to broaden geopolymer applications. In this study, unconventional processing and finishing technologies, such as direct ink printing, drilling, and machining are investigated to demonstrate their suitability for geopolymers. Fly ash-based geopolymers incorporating a relevant amount of waste glass demonstrated suitable flow properties to be used in a direct ink printing process. Moreover, the geopolymer specimens showed high machinability: components were drilled and machined in a lathe obtaining superior surface finish, uniform dimensional accuracy, and complex shape parts. The results presented herein indicate opportunities for expanding applications of geopolymers in areas such as mechanical engineering, where components with accurate, specifically designed shapes and surface finish are needed.
CRIS-Team Scopus Importer:2019-08-13

Verarbeitungstechnologien für Geopolymere: 3D-Druck und mechanische Bearbeitung - Toniolo, Nicoletta; Bednarzig, Vera; Roether, Judith; Rost, Harald; Boccaccini, Aldo R. (Keramische Zeitschrift, 2019)
CRIS-Team Scopus Importer:2019-06-21